Senior Hospital Physician Leaders’ Perspectives on Factors That Impact Physician Engagement: A Qualitative Interview Study - Simard J; Shea C; Cho V; Perrier L; Prokopy M; Moshirzadeh E; Sodhi S; Karsan A; Perreira TA (Dove Medical Press, 2023)
Julie Simard,1 Christine Shea,1 Veronica Cho,2 Laure Perrier,1 Melissa Prokopy,1,2 Emitis Moshirzadeh,2 Sundeep Sodhi,1,2 Alia Karsan,2 Tyrone A Perreira1,2 1Dalla Lana School of Public Health, Institute of Health Policy, Management and Evaluation, University of Toronto, Toronto, Ontario, Canada; 2Ontario Hospital Association, Toronto, Ontario, CanadaCorrespondence: Tyrone A Perreira, Ontario Hospital Association, 200 Front St West, Suite 2800, Toronto, Ontario, M5V 3L1, Canada, Email Tperreira@oha.comBackground: Physicians are essential in health-care delivery. Physician engagement, defined as active participation in administrative and leadership activities in their organization, is a useful metric for hospital leaders to evaluate as they develop and implement strategy. The purpose of this study was to gain insight into the perspectives of senior hospital physician leaders on factors impacting physician engagement.Methods: Semi-structured interviews were conducted virtually. A purposive sample was used. Hospital physician senior leaders were recruited from Ontario public hospitals in Canada. The interviews were recorded, transcribed verbatim, and analyzed.Results: Ten participants in senior hospital physician leadership positions were interviewed. Seven themes were identified as impacting physician engagement: being seen and being heard, accountability, trust, leadership engagement, intercommunication, organizational stability, and discord within the organization. Saturation of themes was achieved.Conclusion: Two-way communication is essential to physician engagement. Physician input in decision-making processes is a vital way to improve engagement. For this to work, leadership must also be engaged. Trust and accountability are critical attributes for senior hospital physician leaders, especially during times of organizational instability. For physicians whose remuneration model is fee-for-service, new compensation models are required for them to actively participate in hospital decision-making.Keywords: physician engagement, hospitals, leadership, interviews as a topic, qualitative research